Conductive super-hydrophobic lithium ion battery diaphragm and preparation method thereof
By using a combination of porous conductive polymer and hydrophobic coating on the lithium-ion battery separator, the problems of high internal resistance, poor high temperature safety and moisture adsorption are solved, and higher battery thermal stability and safety are achieved, and the battery is reduced Internal resistance.
Patent Information
- Application Number
- CN202411316942.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lithium-ion battery separator has problems such as high internal resistance, poor high temperature safety and small contact angle to moisture, which affects battery performance and safety.
A porous conductive polymer separator is combined with a hydrophobic coating. By applying a hydrophobic coating on the porous conductive polymer separator on both sides, excellent lithium ion conduction and high temperature thermal stability are formed, while preventing moisture adsorption.
Improves the thermal stability and safety of lithium-ion batteries, reduces battery internal resistance, and ensures battery consistency and long life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery separators, and in particular relates to a conductive super-hydrophobic lithium ion battery separator and a preparation method thereof. Background Art
[0002] Lithium-ion battery separator is a membrane layer used to separate the positive and negative electrodes of lithium-ion batteries to prevent the two electrodes from contacting and short-circuiting. It also has the function of allowing electrolyte ions to pass through. The material of lithium-ion battery separator is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. The performance of lithium-ion battery separator determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. Lithium-ion battery separators with excellent performance play an important role in improving the overall performance of the battery.
[0003] For lithium-ion batteries, since the electrolyte is an organic solvent system, a diaphragm material that is resistant to organic solvents is required, and a high-strength thin-film polyolefin porous membrane is generally used. Conventional lithium-ion battery diaphragms use aluminum oxide coated on PP or PE to improve the thermal shrinkage of the diaphragm, thereby improving the safety of the battery; there are also organic conductive polymer films used on solid or semi-solid batteries to improve the conduction of lithium ions, thereby increasing the cycle life of the battery. However, the above-mentioned lithium-ion battery diaphragms have the following problems: (1) The insulating barrier effect of the aluminum oxide material itself will increase the internal resistance of the battery; (2) The organic conductive polymer film does not have a stable rigid structure and is easily deformed at high temperatures, resulting in poor high-temperature safety; (3) Both have a small contact angle with water and good adsorption, which poses unpredictable risks to battery performance.
[0004] Therefore, there is a need to improve existing lithium-ion battery separators. Summary of the invention
[0005] In order to solve the above problems of the prior art, the present invention provides a conductive super-hydrophobic lithium-ion battery separator and a preparation method thereof, so as to solve the problems of high internal resistance, poor high-temperature safety and small contact angle with water caused by the lithium-ion battery separator.
[0006] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0007] According to a first aspect of the present invention: a conductive super-hydrophobic lithium-ion battery separator comprises a porous conductive polymer separator and a hydrophobic coating, wherein the porous conductive polymer separator is made by pressing a porous conductive polymer, and the hydrophobic coating is coated on both sides of the porous conductive polymer separator to form a hydrophobic coating on both sides;
[0008] in:
[0009] The thickness of the porous conductive polymer separator is 6 to 25 μm, and the thickness of the hydrophobic coating on each side is 1 to 4 μm:
[0010] The porous conductive polymer separator includes 20-35 parts by weight of an organic conductive polymer, 10-20 parts by weight of β-eucryptite and 40-70 parts by weight of an organic solvent.
[0011] Further, the organic conductive polymer includes 35-40 parts by weight of 3,4-ethylenedioxythiophene, 40-50 parts by weight of polyacrylic acid, 5-8 parts by weight of acrylonitrile monomer, 1-3 parts by weight of benzoic acid peroxide, 0.5-2 parts by weight of phosphorus pentoxide, and 1-3 parts by weight of azobisisobutyronitrile.
[0012] Furthermore, the preparation of the organic conductive polymer comprises the following steps:
[0013] S1: Add 3,4-ethylenedioxythiophene to a reactor containing isopropanol under vacuum and stir, slowly add peroxide benzoic acid dropwise, control the temperature in the reactor to 0-5°C, react for 3-6h, obtain a mixture containing polydithiophene acetic acid and reaction byproducts, then filter out the reaction byproducts, and wash with water to obtain polydithiophene acetic acid;
[0014] S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, raise the temperature to 50-65°C and mix evenly, then add phosphorus pentoxide and raise the temperature to 80-90°C, finally add polyacrylic acid, maintain the pressure at 1.5-2.0 MPa, stir for 4-10 hours to carry out anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration;
[0015] S3: dissolving the acrylic acid-polydithiophene anhydride obtained in step S2 in a chloroform solution under vacuum, adding azobisisobutyronitrile, stirring evenly and controlling the temperature at 10-15°C, slowly dropping acrylonitrile monomer to carry out free radical polymerization reaction, reacting for 10-15 hours and then extracting to obtain an organic conductive polymer.
[0016] Further,
[0017] β-eucryptite is one or more of aluminum eucryptite, magnesium eucryptite, boron eucryptite and aluminum-magnesium eucryptite;
[0018] The organic solvent is one or more of ethylene carbonate, propylene carbonate and polyglycidyl acrylate.
[0019] Further, the hydrophobic coating comprises 10-40 parts by weight of a hydrophobic material, 5-20 parts by weight of a methacrylic resin and 60-85 parts by weight of a solvent;
[0020] The hydrophobic material comprises 10-25 parts by weight of fluorinated paraffin, 12-20 parts by weight of silanized silicon dioxide or dimethyl silicone oil, 0.5-4.5 parts by weight of a silane coupling agent, and 60-75 parts by weight of liquid carbon dioxide.
[0021] Further, the solvent is one or more of DMSO, NMP, THF, DMF and chloroform;
[0022] The fluorinated paraffin wax is one or more of fluorocarbon wax, fluorinated carbonate wax, fluorinated ethylene wax, fluorinated propylene wax, fluorinated ethylene-propylene wax and fluorinated microcrystalline wax.
[0023] Furthermore, the preparation of the hydrophobic material comprises the following steps:
[0024] A1: adding fluorinated paraffin, silanized silicon dioxide or silicon dioxide into a reaction vessel containing liquid carbon dioxide and stirring for 2-4 hours to fully mix to obtain a mixture a;
[0025] A2: Add silane coupling agent to mixture a and stir for 1-2 hours to obtain mixture b;
[0026] A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c;
[0027] A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.75-0.8 MPa, and the D90 particle size is controlled to be 0.6-1.4 microns to obtain a hydrophobic material.
[0028] Furthermore, the preparation of the hydrophobic coating comprises the following steps: adding the hydrophobic material and methacrylic resin into a solvent, stirring at a speed of 800-1200 r / min for 1-3 h under 120 W ultrasound to obtain the hydrophobic coating.
[0029] According to a second aspect of the present invention, a method for preparing the above-mentioned conductive super-hydrophobic lithium-ion battery separator comprises the following steps:
[0030] B1: adding an organic conductive polymer and β-eucryptite to an organic solvent, and homogenizing for 2-4 hours under vacuum to obtain a colloid;
[0031] B2: Place the colloid in an oven at 250-300°C and bake for 3-6 hours to completely evaporate the solvent to obtain a porous conductive polymer;
[0032] B3: hot pressing the porous conductive polymer at a pressure of 20-60 MPa and a temperature of 60-80° C. to obtain a porous conductive polymer separator;
[0033] B4: Coat the hydrophobic coating on the porous conductive polymer membrane at a coating speed of 30-120 m / min. After coating, place it in a vacuum oven at 100-150°C to remove the solvent to obtain a conductive super-hydrophobic lithium-ion battery membrane.
[0034] Furthermore, the coating method is one or more of spray coating, micro-gravure coating, transfer coating and extrusion coating.
[0035] The beneficial effects of the present invention are:
[0036] (1) Organic conductive polymers have excellent lithium ion conductivity due to their unique conjugated π bonds and strong polar group grafting. The compounded rigid structure of β-eucryptite improves the thermal stability of lithium ion battery separators, and has a small high-temperature thermal shrinkage rate. Under the condition of 150℃ / 1h, the transverse and longitudinal thermal shrinkage rates are ≤3.0%, which improves battery safety.
[0037] (2) The hydrophobic coating can effectively prevent the lithium-ion battery separator from absorbing moisture during use and storage, with a contact angle of ≥150° to water, thus improving the battery consistency;
[0038] (3) The strong polar groups of the organic conductive polymer and the hydrophobic coating produce a strong adsorption force to ensure a tight bond, which can control the moisture content to ≤50ppm, eliminating the process of baking the diaphragm in the battery manufacturing process, improving quality and efficiency, and can further reduce the internal resistance of lithium-ion batteries. DETAILED DESCRIPTION
[0039] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods.
[0040] The technical solution of the present invention can be summarized as follows: The present invention provides a conductive super-hydrophobic lithium-ion battery separator and a preparation method thereof, which solves the problems of high internal resistance, poor high-temperature safety and small contact angle with water caused by the lithium-ion battery separator.
[0041] In order to illustrate the scheme and technical advancement of the present invention, the technical scheme and technical application designed are as follows:
[0042] According to a first aspect of the present invention, a conductive super-hydrophobic lithium-ion battery separator comprises a porous conductive polymer separator and a hydrophobic coating, wherein the porous conductive polymer separator is made by pressing a porous conductive polymer, and the hydrophobic coating is coated on both sides of the porous conductive polymer separator to form a hydrophobic coating on both sides;
[0043] Wherein: the thickness of the porous conductive polymer separator is 6 to 25 μm, and the thickness of the hydrophobic coating on each surface is 1 to 4 μm:
[0044] The porous conductive polymer separator includes 20-35 parts by weight of an organic conductive polymer, 10-20 parts by weight of β-eucryptite and 40-70 parts by weight of an organic solvent.
[0045] In the present invention, (1) the amount of organic conductive polymer and β-eucryptite in the porous conductive polymer membrane is preferred, because too much organic conductive polymer will lead to poor air permeability after film formation, and too little organic conductive polymer will lead to poor film structure consistency and poor conductivity; while too much β-eucryptite will lead to uneven film mechanical strength, and too little β-eucryptite will lead to poor thermal stability. (2) Since the melting point temperature, polymerization degree, crystallinity and substitution degree of organic matter are very different, the proportion of different organic matter with different fillers will produce different effects. Therefore, in the present invention, the organic conductive polymer membrane is preferably matched with eucryptite and the amount thereof, which can not only improve the thermal shrinkage rate of the membrane, but also enhance the mechanical properties of the membrane, and can also fill the membrane matrix to prevent the molecular chain from stretching and forming crystal points during high-temperature baking. (3) The preferred thickness of the porous conductive polymer diaphragm is 6 to 25 μm. If the thickness of the diaphragm is too small, the transverse and longitudinal tensile strength is insufficient (less than 190 MPa), the processing performance is poor, and it is difficult to meet the tension requirements of the battery winding and lamination processes; if the thickness of the diaphragm is too large, the volume of the battery will increase and the capacity density will decrease; at the same time, the preferred thickness of the hydrophobic coating is 1 to 4 μm on both sides. If the coating thickness is too small, the hydrophobic effect is not obvious; if the coating is too large, it will affect the overall mechanical strength of the diaphragm because the coating has no mechanical strength.
[0046] Through the technical scheme of the present invention, an organic conductive polymer is used to compound β-eucryptite and a hydrophobic coating. (1) The organic conductive polymer has unique conjugated π bonds and grafted strong polar groups and has excellent lithium ion conductivity. The rigid structure of β-eucryptite can reduce the high-temperature thermal shrinkage rate of the lithium ion battery separator to improve the thermal stability of the lithium ion battery separator. The transverse and longitudinal thermal shrinkage rates are ≤3.0% under the condition of 150°C / 1h, thereby improving the battery safety. (2) The use of the hydrophobic coating can effectively prevent the lithium ion battery separator from absorbing moisture during use and storage, and the contact angle with water is ≥150°, thereby improving the battery consistency. (3) The strong polar groups of the organic conductive polymer and the hydrophobic coating produce a strong adsorption force to ensure close bonding, which can further reduce the internal resistance of the lithium ion battery.
[0047] Preferably, the organic conductive polymer comprises 35-40 parts by weight of 3,4-ethylenedioxythiophene, 40-50 parts by weight of polyacrylic acid, 5-8 parts by weight of acrylonitrile monomer, 1-3 parts by weight of benzoic acid peroxide, 0.5-2 parts by weight of phosphorus pentoxide, and 1-3 parts by weight of azobisisobutyronitrile. The preparation of the organic conductive polymer comprises the following steps:
[0048] S1: Add 3,4-ethylenedioxythiophene to a reactor containing isopropanol under vacuum and stir, slowly add peroxide benzoic acid dropwise, control the temperature in the reactor to 0-5°C, react for 3-6h, obtain a mixture containing polydithiophene acetic acid and reaction byproducts, then filter out the reaction byproducts, and wash with water to obtain polydithiophene acetic acid;
[0049] S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, raise the temperature to 50-65°C and mix evenly, then add phosphorus pentoxide and raise the temperature to 80-90°C, finally add polyacrylic acid, maintain the pressure at 1.5-2.0 MPa, stir for 4-10 hours to carry out anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration;
[0050] S3: dissolving the acrylic acid-polydithiophene anhydride obtained in step S2 in a chloroform solution under vacuum, adding azobisisobutyronitrile, stirring evenly and controlling the temperature at 10-15°C, slowly dropping acrylonitrile monomer to carry out free radical polymerization reaction, reacting for 10-15 hours and then extracting to obtain an organic conductive polymer.
[0051] Through the above technical scheme, an organic conductive polymer is prepared by three-step reaction: (1) Step S1 oxidizes the CC bond connecting the two oxygen atoms of the outer ring into two carboxyl groups through an oxidation reaction. Since the thiophene ring is protected by an isopropanol solution, the thiophene ring can undergo a solution polymerization reaction under the induction of peroxide, but the low-temperature reaction environment needs to be strictly controlled to reduce the generation of by-products; (2) Step S2 is to first react the product of step S1, polydithiophene acetic acid, into an anhydride in an acetone solution, and then graft a strong polar group; phosphorus pentoxide is preferably used as a catalyst because the product obtained in step S1 contains two carboxyl groups that can chelate with phosphorus pentoxide. Therefore, phosphorus pentoxide can preferentially catalyze the two carboxyl groups of the thiophene ring, so that phosphorus pentoxide preferentially reacts with the S1 product with high polarity. Of course, other catalysts can also be used, but other catalysts have relatively poor chelating effects with the S1 product and produce many reaction by-products; (3) Step S3 is to subject the product of Step S2 to a nucleophilic addition reaction with anhydride induced by AIBN, thereby inserting the polar cyano group into the polymer structure and inducing the free radical polymerization reaction of acrylic acid. The two side groups are linked by -CHCN-CHCN-, so that the conductivity of the polymer is further enhanced. In this step, the amount of acrylonitrile added needs to be strictly controlled. If the amount of acrylonitrile added is too fast, it is easy to cause the acrylonitrile to polymerize to form polyacrylonitrile. If the amount of acrylonitrile added is too slow, it is easy to cause insufficient concentration and slow reaction. Preferably, the ratio of the substrate amount (i.e., the total amount of acrylic acid-polydithiophene anhydride, chloroform solution and azobisisobutyronitrile) to the drop rate is: 4000g:2g / s.
[0052] Preferably, the β-eucryptite is one or more of aluminum eucryptite, magnesium eucryptite, boron eucryptite and aluminum-magnesium eucryptite; and the organic solvent is one or more of ethylene carbonate, propylene carbonate and polyglycidyl acrylate.
[0053] Preferably, the hydrophobic coating comprises 10-40 parts by weight of a hydrophobic material, 5-20 parts by weight of a methacrylic resin and 60-85 parts by weight of a solvent; the hydrophobic material comprises 10-25 parts by weight of a fluorinated paraffin, 12-20 parts by weight of silanized silicon dioxide or dimethyl silicone oil, 0.5-4.5 parts by weight of a silane coupling agent, and 60-75 parts by weight of liquid carbon dioxide. The solvent is one or more of DMSO, NMP, THF, DMF and chloroform; the fluorinated paraffin is one or more of a fluorocarbon wax, a fluorinated carbonate wax, a fluorinated ethylene wax, a fluorinated propylene wax, a fluorinated ethylene-propylene wax and a fluorinated microcrystalline wax.
[0054] The preparation of the hydrophobic coating comprises the following steps: adding the hydrophobic material and methacrylic resin into a solvent, stirring at a speed of 800-1200 r / min for 1-3 hours under 120W ultrasound, and obtaining the hydrophobic coating.
[0055] Through the above technical solution, the hydrophobic material is surface-modified with methacrylic resin to make it more evenly dispersed in the solvent; without the surface modification of methacrylic resin, the hydrophobic material is difficult to disperse in the solvent due to agglomeration. At the same time, methacrylic resin also plays a bonding role, and the carboxyl group in it has a good adsorption effect on the diaphragm, ensuring that the hydrophobic coating and the diaphragm have good peel strength and electrochemical stability.
[0056] Preferably, the preparation of the hydrophobic material comprises the following steps:
[0057] A1: adding fluorinated paraffin, silanized silicon dioxide or silicon dioxide into a reaction vessel containing liquid carbon dioxide and stirring for 2-4 hours to fully mix to obtain a mixture a;
[0058] A2: Add silane coupling agent to mixture a and stir for 1-2 hours to obtain mixture b;
[0059] A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c;
[0060] A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.75-0.8 MPa, and the D90 particle size is controlled to be 0.6-1.4 microns to obtain a hydrophobic material.
[0061] Through the above technical scheme, (1) the powder material is uniformly dispersed in the solution through step A1, which is convenient for the cross-linking reaction in step A2, and polar impurities can be separated at the same time; (2) in step A2, the mixture a is cross-linked under the action of a silane coupling agent, and the functional groups such as the methacryloyloxy group of the silane coupling agent are reactive to the organic part and combined, and the Si(OR)3 bond is reactive to the inorganic matter, and the organic matter and the inorganic matter are well connected together to form a more compact hydrophobic structure; (3) step A3 performs carbon dioxide supercritical extraction on the mixture b to separate impurities; (4) the particle size control of the hydrophobic material through step A4 is conducive to the uniform coating of the hydrophobic material on the diaphragm. If the particle size of the hydrophobic material is too small, it will make its specific surface area large and difficult to disperse, and it is easy to agglomerate; if the particle size of the hydrophobic material is too large, it will cause the coating to be not dense enough, and the moisture in the air will easily enter the pores. In this scheme, the preparation of the hydrophobic material requires strict control of the purification process and the particle size of the non-polar hydrophobic material.
[0062] According to a second aspect of the present invention, a method for preparing the above-mentioned conductive super-hydrophobic lithium-ion battery separator comprises the following steps:
[0063] B1: adding an organic conductive polymer and β-eucryptite to an organic solvent, and homogenizing for 2-4 hours under vacuum to obtain a colloid;
[0064] B2: Place the colloid in an oven at 250-300°C and bake for 3-6 hours to completely evaporate the solvent to obtain a porous conductive polymer;
[0065] B3: hot pressing the porous conductive polymer at a pressure of 20-60 MPa and a temperature of 60-80° C. to obtain a porous conductive polymer separator;
[0066] B4: Coating the hydrophobic coating on the porous conductive polymer separator at a coating speed of 30-120 m / min, and placing it in a vacuum oven at 100-150°C to remove the solvent to obtain a conductive super-hydrophobic lithium-ion battery separator. Preferably, the coating method is one or more of spray coating, micro-gravure coating, transfer coating and extrusion coating.
[0067] Through the above technical scheme, the conductive super-hydrophobic lithium-ion battery separator of the present invention is applied to the battery, and the moisture content can be controlled to be ≤50ppm, which reduces the process of baking the separator in the battery manufacturing process, has the effect of improving quality and efficiency, greatly reduces the occurrence of side reactions in the battery cycle, and prolongs the life of the battery. In addition, the traditional separator uses the micropores of the separator for lithium ion conduction, and the separator itself is not conductive. As some electrolyte reaction impurities, lithium dendrites, etc. in the charge and discharge cycle process block the micropores, causing the resistance to become larger and the battery life to decrease; the conductive super-hydrophobic lithium-ion battery separator of the present invention itself is an excellent conductor, and lithium ions can be quickly conducted through polar groups, conjugated double bonds and conductive crystal structures, and lithium ion conduction is smoother, and the influence of electrochemical side reaction impurities is greatly reduced, and the battery resistance is reduced by more than 30%, and the battery life is increased by more than 20%.
[0068] Embodiment 1:
[0069] A conductive super-hydrophobic lithium-ion battery separator comprises: a 6-μm porous conductive polymer separator and a 1-μm hydrophobic coating on both sides.
[0070] Preparation method of porous conductive polymer:
[0071] S1: Add 35 parts by weight of 3,4-ethylenedioxythiophene into a reactor containing isopropanol under vacuum and stir, slowly dropwise add 1.5 parts by weight of benzoic acid peroxide, control the temperature in the reactor to 0°C, react for 3 hours, obtain a mixture containing polydithiophene acetic acid and reaction byproducts, then filter out the reaction byproducts, and wash with water to obtain polydithiophene acetic acid;
[0072] S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, heat to 50°C and mix evenly, then add 0.8 parts by weight of phosphorus pentoxide and raise the temperature to 90°C, finally add 40 parts by weight of polyacrylic acid, maintain the pressure at 1.5 MPa, stir for 6 hours to perform anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration;
[0073] S3: Dissolve the acrylic acid-polydithiophene anhydride obtained in step S2 in chloroform solution under vacuum, add 1.5 parts by weight of azobisisobutyronitrile, stir evenly and control the temperature to 10°C, slowly drop 5 parts by weight of acrylonitrile monomer to carry out free radical polymerization reaction, react for 14 hours and then extract to obtain an organic conductive polymer.
[0074] Preparation method of hydrophobic material:
[0075] A1: 10 parts by weight of fluorocarbon wax and 20 parts by weight of silanized silicon dioxide were added into a reaction vessel containing 70 parts by weight of liquid carbon dioxide and stirred for 2 hours to obtain a mixture a;
[0076] A2: Add silane coupling agent to mixture a and stir for 1 hour to obtain mixture b;
[0077] A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c;
[0078] A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.8 MPa, and the D90 particle size is controlled to be 0.6 microns to obtain a hydrophobic material.
[0079] The preparation of the hydrophobic coating comprises the following steps: adding 10 parts by weight of a hydrophobic material and 5 parts by weight of a methacrylic resin into 85 parts by weight of DMSO, stirring at a speed of 800 r / min for 1 hour under 120 W ultrasound to obtain the hydrophobic coating.
[0080] Preparation method of porous polymer membrane:
[0081] B1: 20 parts by weight of an organic conductive polymer and 10 parts by weight of aluminum eucryptite are added to 70 parts by weight of ethylene carbonate, and homogenized under vacuum for 3 hours to obtain a colloid;
[0082] B2: Place the colloid in an oven at 250°C and bake for 6 hours to completely evaporate the solvent to obtain a porous conductive polymer;
[0083] B3: hot pressing the porous conductive polymer at a pressure of 60 MPa and a temperature of 80 °C to obtain a 6 μm porous conductive polymer separator;
[0084] B4: The hydrophobic coating was coated on both sides of a 6μm porous conductive polymer membrane by spraying at a coating speed of 30 m / min. After coating, the membrane was placed in a vacuum oven at 120°C to remove the solvent. The coating thickness was 1 μm on each side to obtain a conductive super-hydrophobic lithium-ion battery membrane.
[0085] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this embodiment to make a 18650 battery with a capacity of 2200 mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0086] Embodiment 2:
[0087] A conductive super-hydrophobic lithium-ion battery separator comprises: a 16-μm porous conductive polymer separator and a 2.5-μm hydrophobic coating on both sides.
[0088] Preparation method of porous conductive polymer:
[0089] S1: 38 parts by weight of 3,4-ethylenedioxythiophene is added to a reactor containing isopropanol under vacuum and stirred, 2 parts by weight of benzoic acid peroxide is slowly added dropwise, the temperature in the reactor is controlled at 3°C, and the reaction is carried out for 4.5 hours to obtain a mixture containing polydithiophene acetic acid and reaction byproducts, and then the reaction byproducts are filtered out and the polydithiophene acetic acid is obtained after washing with water;
[0090] S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, heat to 55°C and mix evenly, then add 1.4 parts by weight of phosphorus pentoxide and raise the temperature to 85°C, finally add 45 parts by weight of polyacrylic acid, maintain the pressure at 1.8 MPa, stir for 4 hours to perform anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration;
[0091] S3: Under vacuum, the acrylic acid-polydithiophene anhydride obtained in step S2 is dissolved in a chloroform solution, 2 parts by weight of azobisisobutyronitrile is added, the temperature is controlled at 13°C after stirring evenly, 6.5 parts by weight of acrylonitrile monomer is slowly added dropwise to carry out free radical polymerization reaction, and the reaction is carried out for 10 hours and then extracted to obtain an organic conductive polymer.
[0092] Preparation method of hydrophobic material:
[0093] A1: 20 parts by weight of ethylene fluoride wax and 16 parts by weight of dimethyl silicone oil were added to a reaction vessel containing 64 parts by weight of liquid carbon dioxide and stirred for 3 hours to obtain a mixture a;
[0094] A2: Add silane coupling agent to mixture a and stir for 1.5 hours to obtain mixture b;
[0095] A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c;
[0096] A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.75 MPa, and the D90 particle size is controlled to be 1.0 micron to obtain a hydrophobic material.
[0097] The preparation of the hydrophobic coating comprises the following steps: adding 20 parts by weight of a hydrophobic material and 15 parts by weight of a methacrylic resin into 65 parts by weight of NMP, stirring at a speed of 1000 r / min for 2 hours under 120 W ultrasound to obtain the hydrophobic coating.
[0098] Preparation method of porous polymer membrane:
[0099] B1: 30 parts by weight of an organic conductive polymer and 15 parts by weight of aluminum eucryptite are added to 55 parts by weight of propylene carbonate, and homogenized under vacuum for 2 hours to obtain a colloid;
[0100] B2: Place the colloid in an oven at 280°C and bake for 3 hours to completely evaporate the solvent to obtain a porous conductive polymer;
[0101] B3: hot pressing the porous conductive polymer at a pressure of 20 MPa and a temperature of 60 °C to obtain a 16 μm porous conductive polymer separator;
[0102] B4: The hydrophobic coating was coated on both sides of a 16 μm porous conductive polymer membrane using a micro-gravure coating method at a coating speed of 80 m / min. After coating, the membrane was placed in a vacuum oven at 100°C to remove the solvent. The coating thickness was 2.5 μm on each side to obtain a conductive super-hydrophobic lithium-ion battery membrane.
[0103] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this embodiment to make a 18650 battery with a capacity of 2200 mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0104] Embodiment 3:
[0105] A conductive super-hydrophobic lithium-ion battery separator comprises: a 25-μm porous conductive polymer separator and a 4-μm hydrophobic coating on both sides.
[0106] Preparation method of porous conductive polymer:
[0107] S1: Add 40 parts by weight of 3,4-ethylenedioxythiophene into a reactor containing isopropanol under vacuum and stir, slowly dropwise add 3 parts by weight of benzoic acid peroxide, control the temperature in the reactor to 5°C, react for 6 hours, obtain a mixture containing polydithiophene acetic acid and reaction byproducts, then filter out the reaction byproducts, and wash with water to obtain polydithiophene acetic acid;
[0108] S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, heat to 65°C and mix evenly, then add 2 parts by weight of phosphorus pentoxide and raise the temperature to 90°C, finally add 40 parts by weight of polyacrylic acid, maintain the pressure at 2.0 MPa, stir for 10 hours to perform anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration;
[0109] S3: Under vacuum, the acrylic acid-polydithiophene anhydride obtained in step S2 is dissolved in a chloroform solution, 3 parts by weight of azobisisobutyronitrile is added, the temperature is controlled at 15°C after stirring evenly, 8 parts by weight of acrylonitrile monomer is slowly added dropwise to carry out free radical polymerization reaction, and the reaction is carried out for 15 hours and then extracted to obtain an organic conductive polymer.
[0110] Preparation method of hydrophobic material:
[0111] A1: 10 parts by weight of fluorinated microcrystalline wax, 5 parts by weight of fluorinated propylene wax, 5 parts by weight of fluorinated ethylene wax and 20 parts by weight of dimethyl silicone oil were added into a reaction vessel containing 60 parts by weight of liquid carbon dioxide and stirred for 3 hours to obtain a mixture a;
[0112] A2: Add silane coupling agent to mixture a and stir for 2 hours to obtain mixture b;
[0113] A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c;
[0114] A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.78 MPa, and the D90 particle size is controlled to be 1.4 microns to obtain a hydrophobic material.
[0115] The preparation of the hydrophobic coating comprises the following steps: adding 25 parts by weight of a hydrophobic material and 15 parts by weight of a methacrylic resin into 60 parts by weight of DMF, stirring at a speed of 1200 r / min for 3 hours under 120W ultrasound to obtain the hydrophobic coating.
[0116] Preparation method of porous polymer membrane:
[0117] B1: 35 parts by weight of an organic conductive polymer and 20 parts by weight of aluminum eucryptite are added to 45 parts by weight of propylene carbonate, and the mixture is homogenized in a vacuum state for 2 hours to obtain a colloid;
[0118] B2: Place the colloid in an oven at 300°C and bake for 6 hours to completely evaporate the solvent to obtain a porous conductive polymer;
[0119] B3: hot pressing the porous conductive polymer at a pressure of 40 MPa and a temperature of 75 °C to obtain a 25 μm porous conductive polymer separator;
[0120] B4: The hydrophobic coating was coated on both sides of a 25 μm porous conductive polymer membrane by extrusion coating at a coating speed of 120 m / min. After coating, the membrane was placed in a vacuum oven at 150°C to remove the solvent. The coating thickness was 4 μm on each side to obtain a conductive super-hydrophobic lithium-ion battery membrane.
[0121] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this embodiment to make a 18650 battery with a capacity of 2200 mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0122] Comparative Example 1: Compared with Example 2, a conventional PEO+eucryptite (the mass ratio of PEO to eucryptite is 2:1) polymer diaphragm with a thickness of 16 μm was used, and the rest was the same as Example 2.
[0123] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this comparative example to make a 18650 battery with a capacity of 2200 mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0124] Comparative Example 2: Compared with Example 2, no aluminum eucryptite is added during the preparation of the 16 μm porous conductive polymer membrane, and the other conditions are the same as those of Example 2.
[0125] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this comparative example to make a 18650 battery with a capacity of 2200mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0126] Comparative Example 3: Compared with Example 2, a 16 μm porous conductive polymer membrane was prepared without coating the membrane with a hydrophobic coating. Other components were the same as those in Example 2.
[0127] Test results: The internal resistance of the battery was tested by using the lithium-ion battery separator of this comparative example to make a 18650 battery with a capacity of 2200mAh (the main material of the positive electrode is lithium iron phosphate, and the main material of the negative electrode is graphite). The test results are shown in Table 1.
[0128] Table 1
[0129]
[0130] In summary, the embodiments are compared with the comparative examples, and the following conclusions are drawn after analysis:
[0131] 1. From Examples 1 to 3, it can be concluded that as the thickness of the porous conductive polymer membrane increases, the 150°C / 1h transverse and longitudinal thermal shrinkage rate decreases accordingly, and the internal resistance of the battery remains basically unchanged; as the thickness of the hydrophobic coating increases, the contact angle with water increases accordingly, and the moisture content of the membrane also decreases accordingly.
[0132] 2. It can be concluded from Example 2 and Comparative Example 1 that the conductive effect of conventional PEO polymer separators is mainly to reduce the crystallinity of PEO to improve ion conductivity. This method has limitations in improving the conductive effect, such as the crystallinity is too low to form a film-like structure, etc., so the effect of reducing the internal resistance of the battery is not obvious. The present invention itself is an excellent conductor, lithium ions can be quickly conducted through polar groups, conjugated double bonds and conductive crystal structures, lithium ion conduction is smoother, and the influence of electrochemical side reaction impurities is greatly reduced, and the internal resistance of the battery is significantly reduced.
[0133] 3. From Example 2 and Comparative Example 2, it can be concluded that the supporting function of the rigid structure of β-eucryptite in the present invention is to improve the thermal shrinkage rate. If the β-eucryptite is removed, the thermal shrinkage rate will be poor, and the battery will be unsafe when used at high temperatures.
[0134] 4. From Example 3 and Comparative Example 3, it can be concluded that the surface of the porous conductive polymer membrane contains a large number of strong polar groups, and therefore has a strong absorption effect on water. If there is no hydrophobic coating protection, the membrane has a small contact angle with water and a high water content.
[0135] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive super-hydrophobic lithium-ion battery separator, characterized in that: The invention comprises a porous conductive polymer separator and a hydrophobic coating, wherein the porous conductive polymer separator is made by pressing a porous conductive polymer, and the hydrophobic coating is coated on both sides of the porous conductive polymer separator to form a hydrophobic coating on both sides; in: The thickness of the porous conductive polymer separator is 6 to 25 μm, and the thickness of the hydrophobic coating on each side is 1 to 4 μm: The porous conductive polymer comprises 20-35 parts by weight of an organic conductive polymer, 10-20 parts by weight of β-eucryptite and 40-70 parts by weight of an organic solvent.
2. A conductive super-hydrophobic lithium-ion battery separator according to claim 1, characterized in that: The organic conductive polymer comprises 35-40 parts by weight of 3,4-ethylenedioxythiophene, 40-50 parts by weight of polyacrylic acid, 5-8 parts by weight of acrylonitrile monomer, 1-3 parts by weight of benzoic acid peroxide, 0.5-2 parts by weight of phosphorus pentoxide, and 1-3 parts by weight of azobisisobutyronitrile.
3. A conductive super-hydrophobic lithium-ion battery separator according to claim 2, characterized in that: The preparation of organic conductive polymers includes the following steps: S1: Add 3,4-ethylenedioxythiophene to a reactor containing isopropanol under vacuum and stir, slowly add peroxide benzoic acid dropwise, control the temperature in the reactor to 0-5°C, react for 3-6h, obtain a mixture containing polydithiophene acetic acid and reaction byproducts, then filter out the reaction byproducts, and wash with water to obtain polydithiophene acetic acid; S2: Add the polydithiophene acetic acid obtained in step S1 to a reaction kettle containing acetone under vacuum and stir, raise the temperature to 50-65°C and mix evenly, then add phosphorus pentoxide and raise the temperature to 80-90°C, finally add polyacrylic acid, maintain the pressure at 1.5-2.0 MPa, stir for 4-10 hours to carry out anhydride reaction, and obtain acrylic acid-polydithiophene anhydride through extraction and filtration; S3: dissolving the acrylic acid-polydithiophene anhydride obtained in step S2 in a chloroform solution under vacuum, adding azobisisobutyronitrile, stirring evenly and controlling the temperature at 10-15°C, slowly dropping acrylonitrile monomer to carry out free radical polymerization reaction, reacting for 10-15 hours and then extracting to obtain an organic conductive polymer.
4. A conductive super-hydrophobic lithium-ion battery separator according to claim 1, characterized in that: β-eucryptite is one or more of aluminum eucryptite, magnesium eucryptite, boron eucryptite and aluminum-magnesium eucryptite; The organic solvent is one or more of ethylene carbonate, propylene carbonate and polyglycidyl acrylate.
5. A conductive super-hydrophobic lithium-ion battery separator according to claim 1, characterized in that: The hydrophobic coating comprises 10-40 parts by weight of a hydrophobic material, 5-20 parts by weight of a methacrylic resin and 60-85 parts by weight of a solvent; The hydrophobic material comprises 10-25 parts by weight of fluorinated paraffin, 12-20 parts by weight of silanized silicon dioxide or dimethyl silicone oil, 0.5-4.5 parts by weight of a silane coupling agent, and 60-75 parts by weight of liquid carbon dioxide.
6. A conductive super-hydrophobic lithium-ion battery separator according to claim 5, characterized in that: The solvent is one or more of DMSO, NMP, THF, DMF and chloroform; The fluorinated paraffin wax is one or more of fluorocarbon wax, fluorinated carbonate wax, fluorinated ethylene wax, fluorinated propylene wax, fluorinated ethylene-propylene wax and fluorinated microcrystalline wax.
7. A conductive super-hydrophobic lithium-ion battery separator according to claim 6, characterized in that: The preparation of the hydrophobic material comprises the following steps: A1: adding fluorinated paraffin, silanized silicon dioxide or silicon dioxide into a reaction vessel containing liquid carbon dioxide and stirring for 2-4 hours to fully mix to obtain a mixture a; A2: Add silane coupling agent to mixture a and stir for 1-2 hours to obtain mixture b; A3: subjecting mixture b to supercritical carbon dioxide extraction to separate impurities with high polarity, thereby obtaining a purified mixture c; A4: The purified mixture c is sent into a jet milling chamber for jet milling. The chamber pressure is 0.75-0.8 MPa, and the D90 particle size is controlled to be 0.6-1.4 μm to obtain a hydrophobic material.
8. A conductive super-hydrophobic lithium-ion battery separator according to claim 7, characterized in that: The preparation of the hydrophobic coating comprises the following steps: adding the hydrophobic material and methacrylic resin into a solvent, stirring at a speed of 800-1200 r / min for 1-3 hours under 120W ultrasound, and obtaining the hydrophobic coating.
9. A method for preparing a conductive super-hydrophobic lithium-ion battery separator according to any one of claims 1 to 8, characterized in that: The steps include: B1: adding an organic conductive polymer and β-eucryptite to an organic solvent, and homogenizing for 2-4 hours under vacuum to obtain a colloid; B2: Place the colloid in an oven at 250-300°C and bake for 3-6 hours to completely evaporate the solvent to obtain a porous conductive polymer; B3: hot pressing the porous conductive polymer at a pressure of 20-60 MPa and a temperature of 60-80° C. to obtain a porous conductive polymer separator; B4: Coat the hydrophobic coating on the porous conductive polymer membrane at a coating speed of 30-120 m / min. After coating, place it in a vacuum oven at 100-150°C to remove the solvent to obtain a conductive super-hydrophobic lithium-ion battery membrane.
10. The method for preparing a conductive super-hydrophobic lithium-ion battery separator according to claim 9, characterized in that: The coating method is one or more of spray coating, micro-gravure coating, transfer coating and extrusion coating.
Citation Information
Patent Citations
Lithium ion battery separator
CN105336902A
High-performance lithium ion battery diaphragm and preparation method thereof
CN112952289A
Solid electrolytic capacitor
US20090231782A1
Novel separators for electrochemical systems
WO2013154623A1
Cited By
Porous alumina powder applied to lithium ion battery and preparation method of porous alumina powder
CN119994068A
